Pengaruh Penambahan Variasi Konsentrasi Karbon Aktif pada Media Kultur In Vitro untuk Pertumbuhan Anggrek Dendrobium welirang - Andien Narita Putri Warisman; Praptining Rahayu; Eko Retno Mulyaningrum (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to determine the effect of different concentrations of added activated carbon and determine the optimal concentration in the in vitro culture growing medium for Dendrobium welirang orchids to increase plant growth. The type of research used is true experimentation. This research used a Completely Randomized Design (CRD), and the sample used in this research was the orchid species Dendrobium welirang. The instrument used is in the form of a table. The type of data used is quantitative data. The data were analyzed statistically using the ANOVA test. Data collection was carried out in the third month after planting. The data taken includes leaf length, number of leaves, root length, and number of roots. The results of the research showed that adding variations in activated carbon concentration to the in vitro culture medium affected the parameters of root number, root length, leaf length, and number of leaves of the Dendrobium welirang orchid. In conclusion, the addition of activated carbon has a real influence on the growth of Dendrobium welirang orchids. Keywords: Dendrobium welirang, Activated Carbon, In vitro Culture.